2010
DOI: 10.3797/scipharm.1006-02
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of L-Carnitine and Coenzyme Q10 on CCl4-Induced Liver Injury in Rats

Abstract: This study provides an information about the mechanisms of liver injury induced by CCl4, and determines the influence of administration of L-carnitine or/and CoQ10 as prophylactic agents against CCl4 deteriorative effect. The study was carried out on 80 adult male albino rats divided into eight groups, 10 animals each, as follows: four normal groups (control, treated with L-carnitine, treated with CoQ10, and treated with a combination of Lcarnitine and CoQ10) and four liver injury groups treated with CCl4 (con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
28
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 37 publications
(33 reference statements)
4
28
0
2
Order By: Relevance
“…In the current study we observed significant decrease in serum AST concentrations in CoQ10 treated group; in a study, administration of 200 mg/kg CoQ10 as a single dose in cirrhotic rats, reduced serum ALT and AST activities (p<0.05) (Ali et al, 2010). Other studies also reported same results in experimental models (JimenezSanto et al, 2014;Othman et al, 2008).…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…In the current study we observed significant decrease in serum AST concentrations in CoQ10 treated group; in a study, administration of 200 mg/kg CoQ10 as a single dose in cirrhotic rats, reduced serum ALT and AST activities (p<0.05) (Ali et al, 2010). Other studies also reported same results in experimental models (JimenezSanto et al, 2014;Othman et al, 2008).…”
Section: Discussionsupporting
confidence: 77%
“…In another study, administration of 200 mg/kg CoQ10 in cirrhotic rats improved liver enzyme activities compared with control group (Ali et al, 2010). Other animal studies have also confirmed these findings (Sumimoto et al, 1987;Amimoto et al, 1995;Jimenez-Santo et al, 2014) .…”
supporting
confidence: 73%
“…In the present study the hepatotoxic effects of CCl4 were detected by significant elevation in liver enzymes (AST, ALT, and alkaline phosphatase) activities. Several authors have reported a significant increase in liver enzymes in rats subjected to CCl4 intoxication (El-Khatib and Mansour, 2001;Ali et al, 2010). Necrosis or membrane damage in liver releases these enzymes into circulation and hence it can be measured in plasma or serum.…”
Section: Discussionmentioning
confidence: 99%
“…Ali et al (33) have shown that L-carnitine and CoQ 10 have a pronounced prophylactic effect against liver damage induced by halogenated alkanes such as carbon tetrachloride (CCl 4 ). In that study, the investigators pretreated rats with CoQ 10 24 h before the administration of CCl 4 .…”
Section: Discussionmentioning
confidence: 99%